Anaphores argumentatives. Entre l’axe sémantico-pragmatique et l’axe rhétorico-discursif - Collinet, Françoise (Neophilologica, 2016)
This paper focuses on two questions. Firstly, how the use of argumentative anaphora to express an opinion / truth dissociation (Perelman) should be described in terms of grammatical / lexical resources. The other question has a methodological dimension: in which aspects could this approach distinguish itself from linguistic or discursive studies?